WHAT IS THE IMPACT OF AFFECTIVE DISPOSITION ON 4TH-GRADE NAEP READING SCORES? - Peterson, Christina Mollica; Zhang, Mingyuan (International Journal of Research -GRANTHAALAYAH, 2021)
This study presented a secondary analysis of the National Assessment of Educational Progress (NAEP) dataset. The paper examined the impact of affective disposition on 2019 NAEP reading scores of fourth-grade students. In order to gain a better understanding of the impact of affective disposition on the reading achievement of fourth-grade students, this study used a quantitative descriptive research design to analyze secondary data extracted from the 2019 NAEP data set. The results found in this study showed that students’ affective disposition in the areas of making a great effort after making a mistake, continuing to work hard even when they felt like quitting, paying attention and resisting distractions, and feeling happy at school had positive impact on their 2019 NAEP reading assessments scores when the students strongly agreed with the statements. The findings may indicate that improving affective disposition in students may increase reading scores.